A comparative study of efficacy of 0.5% intrathecal isobaric ropivacaine, ropivacaine heavy, and bupivacaine heavy for lower abdomen and lower limb surgeries - Archana Singh; Ashish Mathur; Umesh Prasad Yadav; Preeti Goyal (Asian Journal of Medical Sciences, 2024)
Background: Lower abdomen and lower limb surgeries can be performed under spinal anesthesia. Ropivacaine is a local anesthetic, belonging to the amino amide group. It is a pure S-enantiomer and is considered to have a better safety profile than bupivacaine. Aims and Objectives: The aim of the study is to compare the efficacy of intrathecal isobaric ropivacaine (IR) 0.5%, ropivacaine heavy 0.75% and bupivacaine heavy 0.5% for lower abdomen and lower limb surgeries. Materials and Methods: This prospective randomized study was conducted in 120 patients scheduled for lower abdomen and lower limb surgeries under spinal anesthesia belonging to ASA Grade I or II. Patients were randomized into three groups of 40 each. Group IR-received 3 mL of 0.5% IR, Group hyperbaric ropivacaine (HR)-received 3 mL of 0.75% heavy Ropivacaine and Group Hemoglobin received 3 mL of 0.5% heavy bupivacaine. The parameters studied were the onset and duration of sensory and motor block, duration of analgesia, hemodynamic parameters, and side effects. Results: The onset of sensory and motor block was significantly faster in HR followed by hyperbaric bupivacaine (HB) followed by IR. The duration of sensory and motor block was significantly shorter in HR followed by IR followed by HB. Duration of analgesia was longest in HB. Conclusion: HR produced a rapid onset of the sensory and motor block with a shorter duration. HB produced a longer duration of motor and sensory block.